Antibodies to Staphylococcus aureus Serotype 8 Capsular Polysaccharide React with and Protect against Serotype 5 and 8 Isolates - Park, Saeyoung (Infect Immun, 2014)
Most Staphylococcus aureus isolates produce either a serotype 5 (CP5) or 8 (CP8) capsular polysaccharide, and the CP antigens are targets for vaccine development. Since CP5 and CP8 have similar trisaccharide repeating units, it is important to identify an epitope shared by both CP5 and CP8. To characterize cross-reactivity between CP5 and CP8, the immunogenicity of CP5 and CP8 conjugate vaccines in mice and rabbits was evaluated by serological assays. Immune sera were also tested for functional activity by in vitro opsonophagocytic-killing assays and a murine bacteremia model. Antibodies to the CP5-cross-reactive material 197 (CRM197) conjugate vaccine bound only to purified CP5. In contrast, antibodies to the CP8-CRM conjugate vaccine reacted with CP8 and (to a lesser extent) CP5. De-O-acetylation of CP5 increased its reactivity with CP8 antibodies. Moreover, CP8 antibodies bound to Pseudomonas aeruginosa O11 lipopolysaccharide, which has a trisaccharide repeating unit similar to that of the S. aureus CPs. CP8-CRM antibodies mediated in vitro opsonophagocytic killing of S. aureus expressing CP5 or CP8, whereas CP5-CRM antibodies were serotype specific. Passive immunization with antiserum to CP5-CRM or CP8-CRM protected mice against bacteremia induced by a serotype 5 S. aureus isolate, suggesting that CP8-CRM elicits antibodies cross-reactive to CP5. The identification of epitopes shared by CP5 and CP8 may inform the rational design of a vaccine to protect against infections caused by CP5- or CP8-producing strains of S. aureus.